The solvent action of super oxide vs. sodium hypochlorite on rat dermal connective tissue - a comparative study - Malenab Jr., Virgilio L.
Sodium Hypochlorite (NaOCl) is the most widely used irrigating solution during endodontic procedures because of its efficiency in dissolving organic tissue. However, it is toxic and can cause periapical inflammation once it is extruded beyond the periapex. Super Oxide Water (SOW) on the other hand, carries the properties of Sodium Hypochlorite without its toxic effect. The aim of the study was to compare the solvent action of SOW and NaOCl on rat dermal connective tissue to determine the potential of SOW as an alternative root canal irrigating solution. The tissue samples were immersed in both solutions and the effect of the solvent's action for each group was measured by determining the weight of tissue left thirty minutes after. A t-test was used to determine whether there is a significant difference between the weights of the rat dermal connective tissue exposed to SOW and NaOCl. The results of the study showed that both solutions, SOW and NaOCl dissolved the tissue samples. However, there was significant difference in their dissolving action in favor of NaOCl.